The image of the tyrant and the vanquished in the theatre of Antoine de Montchrestien - Leontaridou, Dora (Romanica Olomucensia, 2017)
The plots of the three Montchrestien tragedies - La Carthaginoise ou la liberte, Les Lacenes, and La Reine d'Ecosse - follow the same pattern: the confrontation of a cruel and tyrannical king with the vanquished. Moreover, in all three tragedies the defeated are women, who show remarkable moral qualities and a heroic attitude towards their destiny. On the other hand, the kings are presented as atrocious and cruel. Conceived after the first period of the religious wars, the tragedies dispute monarchical power.
Keywords: Antoine de Montchrestien; French theatre; 16th century; absolutism; politics; condition of women